PERLINDUNGAN HUKUM ATAS HAK POLITIK PEREMPUAN OLEH NEGARA - Yosefina Daku (University of Udayana, 2015)
As the law states, Indonesia provide the protection of the rights for of all people without the discrimination. By the basis of the mandate of the Preamble to the Constitution of 1945 that